Job Demands, Relational Resources and Job Satisfaction: The Mediating Role of Self Efficacy - Yuliana Ratnasari; Martinus Parnawa Putranta (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2026)
This research investigates employee well-being from an organisational behaviour perspective by examining the impact of job demands and relational resources within educational organisations. It focuses on teachers working in faith-based schools in Java, Indonesia, where strong relational norms, value-based interactions, and close leaders’ member relationships shape everyday work experiences. Specifically, it examines the relationships among work overload, respectful student behaviour, principal support, and teachers’ job satisfaction, with self-efficacy positioned as a mediating psychological mechanism. A quantitative survey was used. Data were collected from 298 teachers across 25 faith-based schools and analysed using PLS-SEM. The findings indicate that work overload is negatively associated with job satisfaction, while respectful student behaviour and principal support are positively associated with job satisfaction. The results further show that self-efficacy mediates the effects of work overload, respectful student behaviour, and principal support on job satisfaction, suggesting that self-efficacy functions as an important psychological resource in managing high work demands and strengthening the benefits of supportive relational environments. Overall, this study highlights the importance of relational resources in sustaining teacher job satisfaction in educational settings and contributes to organisational behaviour and educational management literature by clarifying the mediating role of self-efficacy in the Indonesian faith-based school context.